The role of siblings in talent development: Implications for sport psychologists and coaches - Taylor, R. D.; Collins, D.; Carson, H. J. (Frontiers in Sports and Active Living, 2021)
Developing talent requires consideration of social networks that can facilitate or inhibit progression. Of fundamental influence in this regard is the family, with recent investigation extending its focus from parents to the role of siblings. As such, the purpose of this Conceptual Analysis article is to, firstly, review the characteristics of the sibling relationship that may support or inhibit talent development. Secondly, the analysis then provides empirically derived practical examples to emphasize the holistic and complex role that siblings can play in talent development. Thirdly, strategies are proposed to support practitioners identify specific sibling characteristics, alongside recommendations for how the relationship can be utilized within both the formal and informal environments by coaches and psychologists. Finally, and crucially, important implications of these characteristics are considered to support effective coach and sport psychologist decision making.